"Computer Cowboys" and "Ass-kicking Techno-babes" Challenging Cyberpunk's Conventional Representations of Gender and Sexuality in the Futuristic Digital World of Moxyland. Issue 2 (3rd April 2017) - Wilkinson, Robyn; Stobie, Cheryl
Summary: This article analyses the effects created by Lauren Beukes through her use of the cyberpunk genre in her first novel, Moxyland (2008). Because of its challenge to conventional ideas of embodiment and identity formation, together with its counter-cultural punk ethos, cyberpunk would seem to offer the prospect of transgressive versions of gender and sexuality. However, various critics note that instead of realising this potential, cyberpunk endorses heterosexual masculinity in its narratives, while repressing or marginalising the feminine and homosexual relations. In Moxyland, Beukes actively engages with the conventions of cyberpunk in order to subvert such reactionary reiterations and the conventional gendered power struc-tures that underpin them. Through techniques such as exaggeration, splitting and exploring contrasted forms of masculinity she criticises the cyberpunk genre's conventional treatment of gender, as well as the patriarchal power relations it promotes. Beukes also refutes cyberpunk's tendency to restrict the transgressive potential of its empowered female characters by portraying them in terms of sexualised femininity. She challenges essentialist notions of gender as she depicts women characters in active relation to technology. Her version of the female cyborg conveys a potentially transgressive blending of technology and biology, dramatised outside the conventional lens of the masculine gaze.